À quoi pensent les enseignants quand on leur parle de rituels ? - Marie-Paule Vannier; Maryvonne Merri (Recherches en Éducation)
This article presents an enquiry that was carried out amongst teachers from different educational institutions ranging from kindergarten to high school, including specific specialized education structures, and to whom we questioned rituals in terms of practices they implement in the classroom and the objectifs assigned to these practices. This enquiry, designed and carried out by the collaborative research group Rituels72, contributes to a greater knowledge of school rituals. According to a perspective developed by Lafont (1978), the “ritual” is considered here as a praxeme or “unity to produce meaning” according to material and social personal experiences. The study highlights the salience of belonging to a given institution in the answers brought forth by the teachers. At the same time, this study questions the virtual absence of rituals in certain institutions.